From landscape to philosophical reflection (on the basis of selected poems by Vladimir Beriazev) - Bednarczyk, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The paper presents several ways of transition in a poem, from landscape lyric poetry to philosophical reflection and pondering on human life. The research material included selected pieces by Vladimir Beriazev who is a contemporary Siberian poet. In the course of the analysis, certain characteristic features of poetic strategies were observed, such as coloring manipulation and recurring images.